Coping strategies of older adults with a recent hip fracture within inpatient geriatric rehabilitation. (3rd July 2022) - Scheffers-Barnhoorn, Maaike N.; Sharma-Virk, Manju; van Balen, Romke; van Eijk, Monica; Achterberg, Wilco P.
Abstract: Objectives: Coping strategies may play an important role as facilitator or barrier for functional recovery after hip fracture. This study explored 1] active and passive coping strategies in hip fracture patients within inpatient geriatric rehabilitation (GR) 2] the association of these coping strategies with depression, anxiety, pain and health-related quality of life (HRQoL) Method: Secondary data analysis (FIT-HIP trial). Participants were patients with hip fracture, aged 65+ years, admitted to post-acute GR units. Coping was assessed using the ' Active Tackling ' and ' Passive Reacting ' subscale of Utrecht Coping List (UCL). Depression, anxiety, pain and HRQoL was assessed using GDS-8, HADS-A, NPRS and EQ5D-VAS. Based on UCL norm tables - for both subscales - we dichotomized the group into (extremely) high use of this coping strategy i.e. 'predominantly active coping' (PAC), and 'predominantly passive coping' (PPC); versus their corresponding 'residual groups', i.e. the remaining participants. Results: 72 participants were included. Participants mostly used active coping (PAC: 33.3%), however those engaging in passive coping (23.6%) had significantly more depression and anxiety symptoms (GDS-8 ≥ 3: 31.1% respectively 9.1%, p  = 0.040; HADS- A  ≥ 7: 58.8% vs 10.9%; p  = 0.00). Conclusion: Active tackling and passive reacting coping strategies are used by up to one-third of patients with recent hip fracture. Passive coping was associated with more symptoms of depression and anxiety, which in turn may influence rehabilitation negatively. Screening of (passive) coping strategies could contribute to prompt identification of hip fracture patients at risk for negative health outcomes.